2021
DOI: 10.1186/s13227-021-00182-1
|View full text |Cite
|
Sign up to set email alerts
|

A chelicerate Wnt gene expression atlas: novel insights into the complexity of arthropod Wnt-patterning

Abstract: The Wnt genes represent a large family of secreted glycoprotein ligands that date back to early animal evolution. Multiple duplication events generated a set of 13 Wnt families of which 12 are preserved in protostomes. Embryonic Wnt expression patterns (Wnt-patterning) are complex, representing the plentitude of functions these genes play during development. Here, we comprehensively investigated the embryonic expression patterns of Wnt genes from three species of spiders covering both main groups of true spide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 118 publications
(157 reference statements)
3
25
0
Order By: Relevance
“…Theoretically, differences in the size and position of spider eyes could be achieved through changes in Wnt gene expression patterns. Consistent with this, evidence of divergence in Wnt gene expression was found in a recent study of three species of spiders, including P. tepidariorum [ 58 ]. Furthermore, the regulation of each eye type appears to be mechanistically different, reminiscent of D. melanogaster ( Figure 9 ).…”
Section: Discussionsupporting
confidence: 79%
“…Theoretically, differences in the size and position of spider eyes could be achieved through changes in Wnt gene expression patterns. Consistent with this, evidence of divergence in Wnt gene expression was found in a recent study of three species of spiders, including P. tepidariorum [ 58 ]. Furthermore, the regulation of each eye type appears to be mechanistically different, reminiscent of D. melanogaster ( Figure 9 ).…”
Section: Discussionsupporting
confidence: 79%
“…Given the wealth of genes previously known to be expressed in the SAZ and involved in posterior segmentation, we first examined whether they were markers of these two clusters. We found that Wnt8 [g19404], Wnt11b-2 [aug3.g1356], hh , even-skipped ( eve ) [g21109], runt [g18815], noto1 [g13049], bcl11 [g25539], were all markers of cluster 3 (Fig 5A, 5B) [38, 41, 42, 44, 50, 79]. We also repeated ISH for markers AP2 [aug3.g23531] and g30822 [aug3.g27670] and corroborated their expression in the SAZ (Fig 5C, S9 Fig) [44].…”
Section: Resultsmentioning
confidence: 99%
“…The spatiotemporal analysis of wnt genes expression in the beetle Tribolium castaneum showed that several ligands overlap in the posterior zone, segments/parasegments, and head lobes, suggesting functional redundancy (Bolognesi et al, 2008a). However, when we compiled wnt genes expression patterns including the other panarthropods (Janssen et al, 2010;Hogvall et al, 2014;Janssen and Posnien, 2014;Constantinou et al, 2016;Holzem et al, 2019;Chavarria et al, 2021;Janssen et al, 2021), we found that overlapping is common, although diverse patterns are still observed (Figure 2). Based on the degree of patterning conservation, we were able to classify the expression of Wnt ligands as highly (Wnt1, Wnt5, Wnt6, Wnt7, and Wnt11), moderately (Wnt8, Wnt10, Wnt16, and WntA), and poorly (Wnt2, Wnt4, and Wnt9) conserved, which might suggest that the function of some of these ligands-and not others-would be essential for posterior growth in most panarthropods.…”
Section: The Expression Domains Of Wnt Ligandsmentioning
confidence: 95%
“…The Wnt7 ligand in P. tepidariorum presents duplication, therefore double expression is shown in the scheme (Wnt7.1 is pale brown in the posterior, Wnt7.2 is dark brown in the head). T. castaneum (Bolognesi et al, 2008a); T. platyurus (Constantinou et al, 2016); G. marginata (Janssen et al, 2010;Janssen and Posnien, 2014); P. opilio (Janssen et al, 2021); P. tepidariorum (Janssen et al, 2010;Janssen et al, 2021); E. kanangrensis (Hogvall et al, 2014); H. exemplaris (Chavarria et al, 2021).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation